Experimental Investigation of the Exhaust Device of Turbocharger for Marine Engines - S. Li; Y. Liang; X. J. Hou; X. L. Yang; Y. Q. Wang; Y. Q. Zhao; F. L. Zhang (Journal of Applied Fluid Mechanics, 2023)
In order to reduce the temperature in the marine engine cabin, improve the working environment of the staff and meet the economy and emission requirements, the cooling system of the engine was experimentally investigated in the present study. In this regard, water cooling and air-cooling schemes were studied and the main indicators including engine torque, smoke-emission, and exhaust temperature were analyzed. The obtained results indicate that the highest torque can be obtained from the air-cooling turbine case and air-cooling exhaust pipe. As the applied torque decreases, the outlet smoke first decreases then increases and decreases finally. Moreover, it is found that the water-cooling turbine case and water-cooling exhaust pipe increase the smoke. When the turbocharger is equipped with a water-cooling turbine case and water-cooling exhaust pipe, the higher the engine torque, the higher the turbine exhaust temperature and oil tank temperature, and the greater the reduction of the exhaust temperature. The engine torque is in direct proportion to the fuel consumption. The greater the torque, the higher the engine speed and the greater the fuel consumption. The engine torque is inversely proportional to the fuel consumption rate. The greater the torque, the smaller the fuel consumption rate. In cases with water cooling exhaust devices at 110% loading speed, the temperature after the intercooler is higher than that with the air-cooling exhaust device. After the intercooler, the pressure increases as the applied torque increases, and a higher-pressure ratio can be obtained from the air-cooling exhaust device. The higher the engine torque, the higher the temperature of the turbine exhaust, the higher the outlet temperature of the circulating cooling water, and the higher the temperature in the cabin. It was concluded that the exhaust device of the air-cooling turbine case and water-cooling exhaust pipe can reduce the temperature in the engine parts by up to 2℃, thereby improving the working environment of the cabin staff, economic performance, and the emission index.